Association Between Parents Stimulation Intensity Toward Toddlers’ Development - Eka Anggraeni,; Agusta Dian Elina,; Dedi Saifulah,; Ida Nuryanti,; Bayu Prabowo, (Journal of Health Science Community, 2023)
Lack of early stimulation that can cause children to experience developmental disorders, including some who experience disturbances in motor skills, speech and language skills, social skills and independence. One of the factors that greatly influence the development of toddlers is to be given good stimulation. Literature reviews are carried out based on issues, methodologies, similarities and further research proposals using the Google Scholar data base. Giving stimulation to the development of toddlers varies in everyday life. Education The intensity of parental stimulation on the development of toddlers greatly influences the development of toddlers. From the 5 studies presented, it was found that the role of parents is very important in the intensity of stimulation of toddler development.